RhoA Mediates Epithelial Cell Shape Changes via Mechanosensitive Endocytosis - Cavanaugh, Kate E. (Dev Cell, 2019)
Epithelial remodeling involves ratcheting behavior whereby periodic contractility produces transient changes in cell-cell contact lengths, which stabilize to produce lasting morphogenetic changes. Pulsatile RhoA activity is thought to underlie morphogenetic ratchets, but how RhoA governs transient changes in junction length, and how these changes are rectified to produce irreversible deformation, remains poorly understood. Here, we use optogenetics to characterize responses to pulsatile RhoA in model epithelium. Short RhoA pulses drive reversible junction contractions, while longer pulses produce irreversible junction length changes that saturate with prolonged pulse durations. Using an enhanced vertex model, we show this is explained by two effects: thresholded tension remodeling and continuous strain relaxation. Our model predicts that structuring RhoA into multiple pulses overcomes the saturation of contractility and confirms this experimentally. Junction remodeling also requires formin-mediated E-cadherin clustering and dynamin-dependent endocytosis. Thus, irreversible junction deformations are regulated by RhoA-mediated contractility, membrane trafficking, and adhesion receptor remodeling.